1903 N.J. Laws 671, ch. 257, § 49. - (:unkn) unknown (General Publisher, 1903)
No person shall be entitled to carry or require any company to carry on any railroad any aqua fortis, oil or vitriol, gunpowder, nitro-glycerine, matches, or other goods of a dangerous nature¸ and if any person sends by the railway any such goods without distinctly marking their nature on the outside of the package containing the same, or otherwise giving notice in writing to the agent of the company with whom the same are left at the time of so sending, he shall forfeit to the company twenty dollars for every such offense, and be besides liable to all damage that may occur therefrom, and the company may refuse to take any parcel that they may suspect to contain goods of a dangerous nature or may require the same to be opened to ascertain the fact.
--
Keywords: GUN POWDER TRANSPORTATION